The effect of work engagement on nursing caring behavior with burnout as intervening variables (study of nurses at Datoe Binangkang Lolak Regional General Hospital) - Firda Mokodongan; Heru Kurnianto Tjahjono; Nuryakin Nuryakin (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2021)
Nurse caring behavior is the core of nursing where nurses must be respectful and responsive to patient preferences, values and needs. Caring behavior is influenced by several factors, including workload, lack of time, and burnout. A nurse with a high tendency to burnout will experience loss of motivation, burnout and affect work professionalism, especially on the caring behavior of nurses to patients. This study aims to analyze the effect of work engagement on nurses' caring behavior with burnout as an intervening variable. This research used quantitative with cross sectional approach. The number of samples in this study amounted to 74 nurses. The sampling technique used in this study was purposive sampling. The research instrument used was a questionnaire. The analysis used is path analysis. The result of statistical test of work engagement variable with burnout on nurses has a significant effect in a negative direction. In addition, work engagement with nurses' caring behavior has a significant effect in a positive direction. Meanwhile, burnout with nurse caring behavior has a significant effect in a negative direction. The sobel test results show the effect of work engagement on nurses' caring behavior with burnout as an intervening variable.